Transformasi Pendidikan Berbasis Komunitas Sebagai Katalisator Penguatan Spirit Kewirausahaan dan Inisiasi UMKM Baru di Tingkat Akar Rumput - Hanif, Muh.; Almaududi Ausat, Abu Muna; Suherlan (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to examine how the transformation of community-based education serves as a catalyst in strengthening the spirit of entrepreneurship and encouraging the emergence of new MSMEs at the grassroots level. The method used is a literature review with a qualitative approach and descriptive analysis of 30 scientific articles published between 1994 and 2025, obtained through Google Scholar and other credible websites. Data analysis was conducted using content analysis techniques, namely identifying the main themes of each article to find patterns and connections between concepts. The results of the study indicate that participatory, contextual, and locally rooted community education holds significant potential in shaping entrepreneurial mindsets, fostering social innovation, and strengthening the social capital of communities. The theoretical framework of this study includes Critical Pedagogy Theory, Social Capital Theory, and Social Entrepreneurship Theory, all of which emphasize the importance of experiential and dialogical learning processes in building economic empowerment. Findings from various case studies in Indonesia such as agropreneur communities in Sleman, rattan artisans in Cirebon, and creative MSME actors in Bandung clearly illustrate that community education can be a major driver of new MSME initiation if supported by a collaborative ecosystem and appropriate policy interventions.